Respuestas

2013-09-05T02:15:12+02:00
X^2+y^2+DX+EY+F=0
1)P(2)^2+(-2)^2+D(2)+E(-2)+F=0
4+4+2D-2E+F=0
2D-2E+8+F=0

2)R(1)^2+(4)^2+D(1)+E(4)+F=0
1+16+1D+4D+F=0
D+4E+17+F=0

3)S(4)^2+(6)^2+D4+E6+F=0
16+36+D4+E6+F=0
4D+6E+52+F=0
Eliminando f en 1 y 2
2d-2e-8+f=0
d+4e+17+f=0
-------------------
3d+2e+9+f=0
eliminaando f en 1 y 3
2d-2e-8+f=0
4d+6e+52-f=0
-------------------------
6d+4e+46  =0
6d=46
d=46/6=d=7.66
encontrando e
3d+2e+9+f=0
3(7.66)+2e+9=0
22.98+2e+9=0
2e+31.98=0
e=-31.98/2 E=15.98
encontrando f en 2
d+4e+17+f=0
7.66+4(15.99)+17+f=0
7.66+63.96+17+f=0
f=88.62
ecuacion general
x^2+y^2+dx+ey+f=0
x^2+y^2+7.66x+15.99y+88.62=0